A REVIEW ON RASAYANA WITH SPECIAL REFERENCE TO NUTRACEUTICALS IN THE MANAGEMENT OF DIABETES MELLITUS (AYUSHDHARA, 2017)
Treatment of diabetes is challenging not because of available, safe and effective method; rather, unawareness and denial of this disease add to the treatment challenge. The good news is the incidence of people who were previously unaware or denying they have diabetes has decreased from 30 to 25% over a two-year period. This suggests that efforts to increase awareness are working and people are better prepared to manage the disease and its complications. DM is a chronic condition that results from an inadequate ability or failure to metabolize carbohydrates, fats, and proteins. Because people are so much in diabetes that they are searching for the treatment or rather managing the disease, and for that the concept of nutraceuticals is coming out in the world and wide acceptance is gathered. Indian gooseberry, Jambal fruits, Bengal gram, black gram, mango leaves, string beans, cucumbers, celery, and onions are vegetables and fruits found useful in the treatment of diabetes [Diet Health Club 2008] This concept has been in the Ayurvedic classics since time immemorial and can be understood by the topic Rasayana. In this article how Rasayana can be helpful in Prameha is been studied with the help of recent research in the field of modern medicine.